Peran Kepuasan Pelanggan dalam Memediasi Hubungan antara Kualitas Pelayanan, Pengalaman Pelanggan terhadap Loyalitas Pelanggan - Susetyo, Prabowo Tejo; Handayani, Siti Dyah; Widowati, Retno (Universitas Batanghari Jambi, 2025)
This study aims to analyze the influence of service quality and customer experience on customer loyalty with customer satisfaction as a mediating variable. This study uses a quantitative approach with a survey method of active Shopee and Tokopedia users. The sample was determined using the Lemeshow formula with a total of 97 respondents. Data were collected through questionnaires and analyzed using Structural Equation Modeling (SEM) based on Partial Least Squares (PLS). The results show that service quality and customer experience have a significant effect on customer satisfaction. Customer satisfaction is also proven to have a significant effect on customer loyalty. In addition, service quality and customer experience have a direct effect on loyalty, but are stronger through an indirect path mediated by customer satisfaction. The R² value of 0.945 on customer loyalty indicates that the model has very high predictive ability. This study provides a theoretical contribution by strengthening the understanding of the relationship between service, experience, satisfaction, and loyalty in the context of e-commerce, as well as a practical contribution for digital platform managers to improve service quality and customer experience in order to build long-term loyalty.